2012
DOI: 10.5592/otmcj.2012.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Saw Dust Ash as Partial Replacement for Cement in Concrete

Abstract: o r g a n i z a t i o n , t e c h n o l o g y a n d m a n a g e m e n t i n c o n s t r u c t i o n · a n i n t e r n a t i o n a l j o u r n a l · 4(2)2012 474Saw dust ash, Pozzolan, Workability, Compressive strengthKeywords this research considered the use of saw dust ash as a pozzolan in the production of concrete. the study investigated the physical properties and chemical composition of saw dust ash (SDA) as well as the workability, and compressive strength properties of the concrete produced by replacing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 17 publications
5
44
1
3
Order By: Relevance
“…Sharp decrease in the compressive strength at more than 20% of wood ash replacement levels was observed. The decline of strength with the increase of proportions of ash was reported in many reports (17,18).…”
Section: Discussionsupporting
confidence: 52%
“…Sharp decrease in the compressive strength at more than 20% of wood ash replacement levels was observed. The decline of strength with the increase of proportions of ash was reported in many reports (17,18).…”
Section: Discussionsupporting
confidence: 52%
“…the presence of a higher quantity of SDA will hinder the hydration process to a large extent in spite of its beneficially as a pozzolanic material. This reflected negatively on the compressive strength [43][44][45][46]. Therefore, the big quantities of SDA must be avoided when added to OPC.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…This illustrates that SDA is siliceous and have no hydraulic characteristics. The data shown in Table 3 indicated that the SDA is fit to a large extent with the ASTM Standards to be used as a mineral admixture for cement pastes, mortars or even concretes [31][32][33]. …”
Section: Relation Between Bc Hm Sm Am and Lmmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of agricultural waste materials under research include Saw dust ash (SDA), maize cob ash (MCA) and sugarcane bagasse ash (SCBA).Saw dust ash (SDA) as a potential cement replacement binder has been studied by several researchers for several years. Marthong, Raheem and Sulaiman, Obilade and Nahak and Dash [3,4,5,6] reported that the compaction factor and the compressive strength decreased with increased cement replacement. The optimum SDA cement replacement was 10%.…”
Section: Introductionmentioning
confidence: 99%